Synergistic effects of peripheral GABA and GABA-transaminase inhibitory drugs on food intake control and weight loss in high-fat diet-induced obese mice - Nagao, Tomoka; Braga, Jason D.; Chen, Siyi; Thongngam, Masubon; Chartkul, Maesaya; Yanaka, Noriyuki; Kumrungsee, Thanutchaporn (Frontiers in Pharmacology, 2024)
Background Developing anti-obesity interventions targeting appetite or food intake, the primary driver of obesity, remains challenging. Here, we demonstrated that dietary γ-aminobutyric acid (GABA) with GABA-degradation inhibitory drugs could be an anti-obesity intervention possessing strong food intake-suppressive and weight-loss effects. Methods High-fat (HF)-diet-induced obese mice were divided into six groups receiving either the HF diet or the 2% GABA-HF diet with daily administration of PBS or the GABA-degradation inhibitory drugs, vigabatrin and ethanolamine-O-sulfate (EOS). In 24-h fast-induced refeeding, lean mice with a basal diet were used, and food intake was measured from 0.5 to 24 h after refeeding. Results Coadministration of the 2% GABA-HF diet with vigabatrin or EOS significantly decreased food intake (−53%, −35%) and body weight (−22%, −16%) within 11 days in obese mice, along with a marked increase in plasma GABA levels. Mice receiving dietary GABA alone or the drugs alone exhibited no such effects. Hypothalamic GABA levels increased in drug-treated mice, regardless of diet. At 0.5 h after refeeding, food intake was similar in all groups. However, at 0.5 h, plasma GABA levels were markedly increased only in mice receiving coadministration of dietary GABA and the drugs, and their food intake was completely inhibited for over 6 h, while mice in other groups gradually increased their food intake. Conclusion Combining dietary GABA with GABA-degradation inhibitory drugs effectively suppresses food intake and promotes weight loss in obese mice, primarily through increased plasma GABA availability. These findings may advance the development of food intake-controlling strategies for obesity management.